Statistics for Planning Serial No. 5 Prices Government of Kerala - Planning Commission (Planning Commission, 1972)
The index number of Parity indicates the level of the prosperity of the farmer. Though one may feel that the prices received by the farmers would indicate the level of the prosperity, the prices received do not by themselves give an idea of the prosperity of the farmers unless these are studies in relation to the prices paid by them on items entering into domestic and farm expenditure. Changes in the relative levels of prices received and prices paid by the farmers in relation to a base period can best be measured by the index of parity between these two.
State Planning Board and The Bureau of Economics and Statistics Kerala